Low cycle fatigue behaviour of a single crystal Ni-based superalloy with a central hole: Effect of inhomogeneous rafting microstructure. (December 2021) - Yang, X.G.; Tan, L.; Sui, T.X.; Shi, D.Q.; Fan, Y.S.
Highlights: LCF properties of a SC Ni-based superalloy with a central hole after different pre-rafting treatments were investigated. The variation and spatial distribution of microstructural rafting near the central hole were captured by the FE-SEM approach and an image processing algorithm. The role of the inhomogeneous rafting on LCF life and crack propagation behaviours were investigated. An analytical model to bridge the inhomogeneous rafting and LCF life reduction was proposed based on the critical distance theory. Abstract: To revealing the role of unevenly microstructural rafting caused by stress gradient on the fatigue resistance of engineering parts made by single crystal (SC) Ni-based superalloys, a stress-control low cycle fatigue (LCF) experiments were performed at 980 °C with a 0.1 stress ratio of central-hole specimens that underwent different pre-rafting treatments. An image process algorithm and field emission scanning electron microscope (FE-SEM) were employed to given a quantitative description of the rafting field near the central hole experimentally. Within half radius of the central hole, the rafting state defined in the present work presents obvious gradient, which disappears with the deterioration of rafting conditions. The rafting morphology tends to be uniform that weakens the effect of inhomogeneous rafting microstructure on LCF resistance as the rafting state exceeds 0.6. The worsening of fatigue resistance is ascribed to the comprehensive degradation effect of rafting, even resulting in 90% reduction of fatigue life compared with the virgin state. Moreover, it was found that rafting changed the initial orientation of fatigue cracks, whereas the crack always propagated along the boundary of micro twins at the late life stage. Finally, an analytical model was proposed to given a quantitative linkage between the inhomogeneous rafting microstructure and the reduction of fatigue resistance.